The Cultural and social impacts of male infertility on them and their spouse in patriarchal societies; A systematic Review - Hanna Khair1*, Aftab Ahmed2 Hazoora Shaikh3, Salma4, Saba leeza5, Faiqa Memon6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Background: Male infertility may be a worldwide regenerative health issue. Helping give or take half for infertility around the world. Conveyance of effective, handy personal satisfaction and safe health benefits may be a standout amongst those building blocks for globe Health. Enhanced caliber from claiming health awareness conveyances will improve usage for health care service. Furthermore, it can move forward to psychosocial and also economic measures for community. Literature is reviewed through systematic search from three data bases “PuBMed”, and “Cinahle”. Thoroughly studying all articles found relevant to the search topic and review question. Articles excluded from the review were on the basis of exclusion criteria. the term included was “Male infertility” after that “Male Infertility” AND “Perception” was entered finally “Male Infertility” AND “Perception” AND “Impact”. The full Search term as “male infertility” AND "Perception" AND "Impact" AND “male infertility” AND "Perception"”. Results: Many findings suggest that if men perceive or diagnosed sole responsible for infertility in couples they have less control on life, they are unable to meet life achievement and perceive themselves responsible for infertility. Some of the studies do not have findings on men’s psychological and social issue but yet it has proven that main on these domains face more problems than women. Conclusion: There can be interventional applications to cast off and improve those challenges. The findings provide convincing evidence that sexual and personal existence for the male companions of infertile couples is affected in event that they understand that they’re reason of infertility. because of loss of clean diagnosis and it is related to increase social pressure in these men.